Finnish National Foresight Process and Practices for Evident-Based Decision-Making – How to Include Future Generations? - Heinonen Sirkka (Instituto Vasco de Administración Pública (IVAP), 2025)
This article presents an overview of the Finnish government and parliamentary foresight: its origin and motivation, as well as organization, agency, process and practices. The national foresight ecosystem provides the framework for government and public foresight work i.e. for policy foresight and related decision-making. Two forward-looking mechanisms which were specially introduced to support public decision-making are presented: 1) the Prime Minister’s Office and Government Reports on the Future, and 2) the Committee for the Future in Parliament. We need anticipatory governance. To all governments, to all governance in cities, nations, organisations – systematic futures approaches and methods should be introduced. Each country could also thrive100 from establishing a Society for Futures Studies as Finland did in 1980, comprising members from very different backgrounds into an inclusive futures dialogue via seminars, publications etc. Currently, we are living the age of deep uncertainty when proactive preparation for various unexpected futures is crucial. Moreover, futures resilience is the capacity needed for anticipating such crises, coping with them, learning from them, and for reorganisation. We need to make today’s decisions as bearing in mind the governance for the futures. Accordingly, the most recent challenge is to include future generations into this foresight mechanism. For public foresight, facts as evidence matter most. However, in order to adequately scan alternative future developments and to have conversations on what policies are needed to tackle those, also imagination is needed. Furthermore, policy-makers themselves could benefit from the knowledge and applications of foresight methods, not just from using foresight studies.